2016
DOI: 10.1039/c6fo00051g
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of spinach (Spinacia oleracea L.) phytochemicals and bioactives

Abstract: Overwhelming evidence indicates that diets rich in fruits and vegetables are protective against common chronic diseases, such as cancer, obesity and cardiovascular disease. Leafy green vegetables, in particular, are recognized as having substantial health-promoting activities that are attributed to the functional properties of their nutrients and non-essential chemical compounds. Spinach (Spinacia oleracea L.) is widely regarded as a functional food due to its diverse nutritional composition, which includes vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
142
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(149 citation statements)
references
References 91 publications
3
142
0
4
Order By: Relevance
“…104 Although bioactive compounds in isolation can have wide-reaching health benefits through antioxidant and anti-inflammatory actions, they are known to act additively and synergistically to elicit a more pronounced biological effect when consumed together. 105,106 A recent study demonstrated that grape seed phenolic extract that contains many phytochemicals positively influenced bone healing by increasing the mechanical strength of the healing femur. 107 Though these compounds show some promise in pre-clinical animal studies, several important questions remain (Fig.…”
Section: Emerging Areas and Future Perspectives Nontraditional Dietarmentioning
confidence: 99%
“…104 Although bioactive compounds in isolation can have wide-reaching health benefits through antioxidant and anti-inflammatory actions, they are known to act additively and synergistically to elicit a more pronounced biological effect when consumed together. 105,106 A recent study demonstrated that grape seed phenolic extract that contains many phytochemicals positively influenced bone healing by increasing the mechanical strength of the healing femur. 107 Though these compounds show some promise in pre-clinical animal studies, several important questions remain (Fig.…”
Section: Emerging Areas and Future Perspectives Nontraditional Dietarmentioning
confidence: 99%
“…Low in cost and easily accessible (Van Duyn & Pivonka, ), green leafy vegetables are sources of important vitamins, minerals, fibre and essential amino acids (McMahon et al, ; Pandey, Ganeshpurkar, Bansal, & Dubey, ; Walorczyk, ), and they also provide nonnutrient biologically active components such as phytochemicals (e.g. polyphenols and flavonoids; NSW Department of Health, ; Roberts & Moreau, ; Van Dokkum, Frølich, Saltmarsh, & Gee, ). These components act as antioxidants and prevent the influence of free radicals on biomolecules such as fats, deoxyribonucleic acids and proteins (Farina, Abdullah, Bibi, & Khalik, ).…”
Section: Green Leafy Vegetables and Their Diverse Importancementioning
confidence: 99%
“…Spinach is primarily composed of water (91.4%) and contains small amounts of protein (2.9%), carbohydrate (3.6%), and fat (0.4%). In addition, spinach have functional properties such as antioxidant, anti-inflammatory, antiproliferative, anti-obesity, hypoglycemia, and lipid-lowering activities (Roberts & Moreau, 2016). Spinach (100 g serving) contains 2.2 g fiber, meeting 8.8% of the recommended dietary allowance for a 2,000 kcal diet.…”
mentioning
confidence: 99%
“…Spinach (100 g serving) contains 2.2 g fiber, meeting 8.8% of the recommended dietary allowance for a 2,000 kcal diet. In addition, spinach have functional properties such as antioxidant, anti-inflammatory, antiproliferative, anti-obesity, hypoglycemia, and lipid-lowering activities (Roberts & Moreau, 2016).…”
mentioning
confidence: 99%